Analysis of gold investment with installment scheme - Rifqi, Latif Hanafir; Mufiroh, Lia Anissatun; Nihayah, Ana Zahrotun (Journal of Islamic Economics Management and Business (JIEMB), 2021)
Investment is an activity of placing part of one’s wealth to gain profits in the future. One investment instrument that is in great demand by the public is a gold investment. This paper aims to analyze  the advantages and disadvantages of the gold investment model with the installment mechanism. This research uses a qualitative approach by exploring scientific sources associated with golden installments. Analysis using the strengths, weaknesses, opportunities, and threats. The object of analysis is limited to gold installment products in Bank Syariah Indonesia. The analysis results on the strength aspect, among others, found that the installment value gold is permanent and light, guarantees security in gold storage, and is convenient how to invest for beginners. On the aspect of weakness, there is a down payment and procurement auctions in the event of default. The aspect of opportunity that can be done is the value of The public’s gold investment needs are quite high, the profit value is relatively stable obtained by customers, relatively easy gold buying and selling transactions, the tendency of rising prices gold in each period, the level of competition in the gold installment market has not been so competitive. Meanwhile, in the treatment aspect, there is the potential for the growth of similar products from producers or other financial institutions and a decline in world gold prices. The research results are beneficial to customers and BSI. For (prospective) consumers, it can be used as material in deciding whether to invest or not. For BSI, it can be used as information related to modifying the gold installment investment scheme.